Nuclearity, structure and properties of tiara-like complexes - Martin, Harry J. (2018)
The work in this thesis principally describes the synthesis and formation of a series of tiara- like complexes, a class of cyclic transition metal complexes of varying sizes. Despite the numerous examples of this class of complex within the scientific literature, little to no control over the size of the reported molecules is reported. This work aims to attain some degree of selectivity over the nuclearity of the synthesised complexes by two methods; firstly, the modification of reaction conditions with a focus on the choice of solvent used for the synthesis and the second method involving a modification of the structure of the ligand used.